Risk Factors for Diabetes Mellitus Patients Against Covid-19 - Jasmin Ananda Wulan; Afrita Amalia Laitupa; Kartika Prahasanti (Universitas Muhammadiyah Surabaya, 2021)
ABSTRACTCovid-19 patients with Diabetes mellitus (DM) ranked third after hypertension and cardiovascular disease with an estimated 36% of all Covid-19 cases. These patients have a risk of experiencing a higher complication possibility since their metabolic disorder can cause hyperglycemia to the patient. It is showed that the number of deaths reached 7,3%, which is higher than non-diabetes. The increase of DM patients caused by stress factors may trigger the onset of glucose in blood sugar, and the glucose variability became abnormal. This circumstance may cause a glycemic increase that causes the predisposition intensification of susceptible affected by Covid-19. Good management is truly needed for DM patients affected by Covid-19. It is hoped to reduce the risk factor, such as preventing complications and increasing life quality by regular medical check to have a good prognosis. Some research showed that Covid-19 patients with DM are essential in ICU and need more treatment attention as they may experience Acute Respiratory Distress Syndrome (ARDS). Diabetes mellitus patients' treatment strategy is to manage the blood glucose level, especially in post-prandial glucose. This literature aims to know the degree of serious illness of Covid-19 patients by the comorbidity of DM in this pandemic event. Keywords: Covid-19, Sars-Cov-2, Diabetes Mellitus, risk factors,Correspondence: jasminananda@gmail.com